Model Hubungan Diameter–Tinggi Pohon Sengon pada Hutan Rakyat di Desa Condong, Kabupaten Probolinggo: Diameter–Height Relationship Model of Sengon Trees in Smallholder Forests in Condong Village, Probolinggo Regency - Yandi, Wahyu Nazri; Oktaviarini, Maulida (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Smallholder forests in Condong Village, Probolinggo, play a vital role in providing Sengon timber, yet farmers often face challenges in accurately estimating tree height, leading to low bargaining power in timber transactions. This study aims to develop a site-specific diameter-height (D-H) relationship model as a practical height estimation instrument for farmers. Data were collected from 130 Sengon trees, categorized into modeling (70%) and validation (30%) datasets. Seven models, including linear and non-linear models (such as Power, Weibull, and Naeslund), were evaluated using Root Mean Square Error (RMSE), Adjusted R-Squared (R2adj), and Akaike Information Criterion (AIC). This model accurately represents the asymptotic biological growth characteristics of Sengon, where height growth slows as diameter increases. The implication of this study is the availability of an accurate self-inventory tool for farmers to enhance transparency and bargaining power in bulk timber sales. Keywords: Falcataria moluccana, non-linear model, smallholder forest, diameter, tree height. ABSTRAK Hutan rakyat di Desa Condong, Probolinggo, memiliki peran vital dalam penyediaan kayu sengon, namun petani sering menghadapi tantangan dalam mengestimasi tinggi pohon secara akurat, yang berdampak pada rendahnya posisi tawar dalam transaksi kayu. Penelitian ini bertujuan untuk membangun model hubungan diameter-tinggi (D-H) yang spesifik lokasi sebagai instrumen praktis penduga tinggi pohon bagi petani. Data dikumpulkan dari 130 pohon sengon yang dibagi menjadi data pemodelan (70%) dan validasi (30%). Tujuh model, termasuk model linear dan non-linear (seperti Power, Weibull, dan Naeslund), dievaluasi menggunakan kriteria Root Mean Square Error (RMSE), Adjusted R-Squared (R2adj), dan Akaike Information Criterion (AIC). Model ini secara akurat merepresentasikan karakteristik biologis pertumbuhan sengon yang bersifat asimtotis, di mana pertambahan tinggi melambat seiring meningkatnya diameter. Implikasi dari penelitian ini adalah tersedianya alat inventarisasi mandiri yang akurat bagi petani untuk meningkatkan transparansi dan posisi tawar dalam penjualan kayu secara borongan. Katakunci: Falcataria moluccana, model non-linear, hutan rakyat, diameter, tinggi pohon.